IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN KOTA SEMARANG (KAJIAN PERATURAN DAERAH KOTA SEMARANG NO. 4 TAHUN 2008 TENTANG PENANGGULANGAN KEMISKINAN) - Derlauw, Voni Hardila Iswari; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Poverty is a problem in Indonesia, which until now hasn’t been resolved. Semarang is a city with the highest poverty rates in Central Java. . To tackle poverty in Semarang city, the government issued Regional Regulation No. 4 Year 2008 on poverty reduction in Semarang city with the aim of reducing the number of poor people. This research using type descriptive with a qualitative approach. Technique data collection used the interview, observation, documentation and literature study. The result of this research show that policy implementation of poverty reduction in Semarang can still be said to be less effective because of assistance from the government is still a lot that can not be perceived by the public. The aspects that became an obstacle in the implementation of this policy is the aspects communication, resources, standard and objectives and attitude. It needs a review routinely in the implementation not only at the beginning of its formation, and the increase in socialization on the aid in poverty reduction policies .